Rule of law in international law and its application in practice - Dugajlić, Stefan (Glasnik Advokatske komore Vojvodine, 2021)
The subject of the article is to point out that the rule of law, often characterized as a national concept, cross the national borders of sovereign states, and that field of rule of law has a direct impact on international law, relations between states, individuals and states and between individuals. The increasing and more frequent interaction of the above subjects in international relations has led to the need to constitute certain rules - regulations, more precisely international law, and to ensure its enforcement, and to protect the subjects from possible violations of it. The rule of law becomes even more represented at the international level, with the establishment and later with the activities of international organizations such as: United Nations, Council of Europe, European Union. By acceding to that organisations, by actively participating in law decisions, directly or through ratification, states in some way renounce the acts of their sovereignty, accepting and enforcing that regulations, and giving them higher place in the hierarchy of regulations than national law. This article describes the path of the rule of law from the Grand Charter of Freedoms (Magna Carta Libertatum), as a national concept, to the present where the rule of law has a strong and indispensable influence in creation, enforcement and protection of international regulations.